WAKTU LUANG ANAK JALANAN PENJUAL KORAN - Amirul Bayu Kurniawan; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Adrianto, Reza, Kevin, and Ganda are ordinary kids who decided to sell newspapers on the streets after school hours to earn money to enhance their pocket money, purchase credits, or also playing playstation and others. The status and role of school students also is an issue that should be used to redefining the meaning of street children. On the other hand, their activities as newspaper seller and school liability does not preclude the influence of globalization and westernization. The mass media and mass culture have an influence on their lifestyle and the selection of food consumption, consumption goods, and their leisure time activities. The Label as street children is not necessarily rule out the possibility to own and use their spare time. Although a leisure activity is more synonymous with entertainment and recreational activities are easily found on the upper middle class society. Leisure time that possessed by these kids are different from the children of the middle class. Although they were busy with the activity of selling newspapers still had time to enjoy the spare time that would had been adjusted to the role and status as a student and newspaper's seller. Their leisure time activities can be grouped based on the unity of units, frequency, planning, funding, and based on its purpose.Keywords: Street Children, Newspaper Seller, Lifestyle, Leisure Time